Onset time and characteristics of postprocedural bleeding after endoscopic resection of colorectal lesions: a multicenter retrospective study - Xiao, Qiyun; Eckardt, Maximilian; Mohamed, Awsan; Ernst, Helmut; Behrens, Alexander; Homann, Nils; Hielscher, Thomas; Kähler, Georg; Ebert, Matthias; Belle, Sebastian; Zhan, Tianzuo (Digestive diseases, 2023)
Introduction: Postprocedural bleeding is a major adverse event after endoscopic resection of colorectal lesions, but the optimal surveillance time after endoscopy is unclear. In this study, we determined onset time and characteristics of postprocedural bleeding events. Methods: We retrospectively screened patients who underwent endoscopic resection of colorectal lesions at three German hospitals between 2010 and 2019 for postprocedural bleeding events using billing codes. Only patients who required re-endoscopy were included for analysis. For identified patients, we collected demographic data, clinical courses, characteristics of colorectal lesions, and procedure-related variables. Factors associated with late-onset bleeding were determined by univariate and multivariate logistic regression analysis. Results: From a total of 6,820 patients with eligible billing codes, we identified 113 cases with postprocedural bleeding after endoscopic mucosal (61.9%) or snare resection (38.1%) that required re-endoscopy. The median size of the culprit lesion was 20 mm (interquartile range 14-30 mm). The median onset time of postprocedural bleeding was day 3 (interquartile range: 1-6.5 days), with 48.7% of events occurring within 48 h. Multivariate logistic regression analysis demonstrates that a continued intake of antiplatelet drugs (OR: 3.98, 95% CI: 0.89-10.12, p = 0.025) and a flat morphology of the colorectal lesion (OR: 2.98, 95% CI: 1.08-8.01, p = 0.031) were associated with an increased risk for late postprocedural bleeding (>48 h), whereas intraprocedural bleeding was associated with a decreased risk (OR: 0.12, 95% CI: 0.04-0.50, p = 0.001). Conclusion: Significant postprocedural bleeding can occur up to 18 days after endoscopic resection of colorectal lesions, but was predominantly observed within 48 h. Continued intake of antiplatelet drugs and a flat polyp morphology are associated with risk for late postprocedural bleeding.
Gesehen am 05.12.2023